Deemed Consent in Islamic Banking from Contract Law Perspective: A Sharia Analysis (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This paper is specifically focusing on the issue of deemed consent as applied in modern Islamic financial contracts. It has been recognized by some scholars and rejected by others. The purpose of this study is to examine the meaning of deemed consent in contract law and its recognition from the Sharia point of view. It begins with examining the meaning of sighah and deemed consent from civil law as well as Islamic law perspective and followed by the analysis of the effect of silence in the validity of acceptance in Islamic law of contract. The approach that is applied in this study is qualitative research in nature, with regards to documentation and secondary sources by reviewing and analyzing the fiqhi perspective of consent and silence in Islamic law; by taking into consideration current practice of financial industry. The findings of the study are that deemed consent in the law can be considered as an acceptance. It is understood by the buyer indicating his consent to the sale by his conduct or silence. Generally, absolute silence in banking transactions is not an acceptance, but that there must be evidences or clues indicating the consent of customers. As such the non-absolute silence can be considered as acceptance in the Islamic law by taking into consideration some Sharia parameters proposed in this study. Interestingly, this idea is also shared by the Common law. Accordingly, based on the analysis conducted in this study, tacit acceptance, or implied acceptance is one of the means of expressing contemporary consent that can be applied. This study develops Sharia parameters consisting of five items as important guidelines in applying deemed consent in the Islamic banking.
Keywords: Deemed consent; implied acceptance; tacit acceptance; ijab qabul; Islamic banking